1992
DOI: 10.1021/tx00028a008
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation of methyl oleate in hexane, in a thin film, in SDS micelles, and in distearoylphosphatidylcholine liposomes: yields and properties of the Criegee ozonide

Abstract: We here explore the use of Criegee ozonides as markers of ozone damage to lipids in systems that model pulmonary surfactant, lung lining fluids, and/or pulmonary membranes. Ozonation of methyl oleate in hexane gives an 89% yield of the Criegee ozonide. The presence of water should reduce the yield of this ozonide, and as expected, small but significant yields of Criegee ozonides are formed when the ozonation of methyl oleate is carried out as a film over phosphate buffer, in aqueous micelles of sodium dodecyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…The CID spectrum of the [M+H] + ion of m/z 808 had product ions at m/z 184, 621, 650 and 666, which correlated to the 1,2,4-trioxolane structure (Criegee ozonide) being present at the 9-carbon at a 18-carbon chain (addition of three oxygen atoms (48 u) to PC 16:0_18:1, m/z 760) (Figure 3). The two HPLC peaks had no apparent differences in product ion spectra suggesting presence of cis and trans structures as observed previously [27]. …”
Section: Resultssupporting
confidence: 74%
“…The CID spectrum of the [M+H] + ion of m/z 808 had product ions at m/z 184, 621, 650 and 666, which correlated to the 1,2,4-trioxolane structure (Criegee ozonide) being present at the 9-carbon at a 18-carbon chain (addition of three oxygen atoms (48 u) to PC 16:0_18:1, m/z 760) (Figure 3). The two HPLC peaks had no apparent differences in product ion spectra suggesting presence of cis and trans structures as observed previously [27]. …”
Section: Resultssupporting
confidence: 74%
“…The fact that SOZ is still observable at 1.4 Â 10 17 molecules H 2 O cm À3 (20% RH) shows that the CI is not completely trapped by water, and some CI can still recombine with the aldehyde. Similar observations were made for the ozonolysis of POPC liposomes in aqueous solution 94 and methyl oleate in aqueous micelles of sodium dodecyl sulfate 95 where the yields of SOZ were 11%, compared to 89% for the methyl oleate reaction in hexane. SOZ production was also observed in the reaction of O 3 with 1-palmitoyl-2-oleoyl-sn-phosphatidylglycerol surfactant on a 1 : 1 water-methanol solution.…”
Section: Kineticssupporting
confidence: 75%
“…94 and methyl oleate in aqueous micelles of sodium dodecyl sulfate 95 where the yields of SOZ were 11%, compared to 89% for the methyl oleate reaction in hexane. SOZ production was also observed in the reaction of O 3 with 1-palmitoyl-2-oleoyl-sn-phosphatidylglycerol surfactant on a 1 : 1 water-methanol solution.…”
Section: Kineticsmentioning
confidence: 95%
“…Only a small number of studies have investigated the effectiveness of ozone therapy on periodontal parameters. The approach was expected to significantly improve the glycated hemoglobin (HbA1C) level [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Our results showed that both treatments resulted in significant improvements in all clinical and biochemical parameters, showing no significant difference between the conventional periodontal treatment and the treatment with a conjunction of gaseous ozone after 12 months.…”
Section: Discussionmentioning
confidence: 99%